Application of model based systems engineering for the conceptual design of a hybrid-electric Atr 42-500: from system architecting to system simulation - Cappuzzo, Federico; Broca, Olivier; Vouros, Stavros; Roumeliotis, Ioannis; Scullion, Calum (American Society of Mechanical Engineers (ASME), 2021)
The progress in aerospace technology over the recent years led to the development of more sophisticated and integrated systems. To cope with this complexity, the aerospace industry is seeing a progressive trend towards adopting Model-Based Systems Engineering (MBSE) in various stages of the product development cycle. The ability to capture emerging behavior, mitigation of risk and improved communication among different stakeholders are some key benefits that MBSE provides over traditional methods for complex systems and processes. This paper attempts to bridge the gap between system architecting and system simulation activities by proposing a methodology to facilitate seamless flow of information between the two development aspects. This methodology was applied to the development of a parallel hybrid-electric version of the ATR 42–500. The use case was designed for a regional mission of 400 nautical miles with the ability to meet regulation requirement of carrying enough reserves for landing at an alternate airport. An integrated systems model, consisting of gas turbine engine, electric powertrain, and flight dynamics, was developed with Simcenter Amesim to analyze the dynamics performance of the aircraft throughout the whole mission. The key metrics evaluated were fuel consumption, take-off weight and the Energy Specific Air Range (ESAR) of the aircraft. As environmental regulations are becoming more stringent, pollutant and noise emissions were considered in the study. The most promising hybrid configurations are recognized, the potential benefits are quantified highlighting the strong potential of System Architecting and System Simulation to provide valuable insights early in the development cycle, reducing the time and cost of product development.
Keywords: MBSE; system architecture; system simulation; hybrid aircraft; aircraft performance; simcenter amesim